Mission to the Volga - Ibn Fadlan, Ahmad, active 922; Montgomery, James E. (James Edward), 1962-; Toorawa, Shawkat M.; Severin, Timothy (New York : New York University Press, 2017)
'Mission to the Volaga is the oldest surviving instance of sustained first-person travel narrative in Arabic--a pioneering text of peerless historical and literary value ... In this colorful documentary from the tenth century, the enigmatic Ibn Fadlan relates his experiences as part of an embassy sent by Caliph al-Muqtadir to deliver political and religious instruction to the recently-converted King of the Bulghars. During eleven months of grueling travel, Ibn Fadlan records the marvels he witnesses on his journey, including an aurora borealis and the white nights of the North. Crucially, he offers a description of the Viking Rus, including their customs, clothing, body painting, and a striking account of a ship funeral. Together, these anecdotes illuminate a vibrant world of diversity during the heyday of the Abbasid Empire, narrated with as much curiosity and zeal as they were perceived by its observant beholder.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Ibn Fadlan, Ahmad, -- active 922 -- Travel -- Asia, Central; Bulgars (Turkic people) -- Russia (Federation) -- Volga River Region -- History; Volga River Region (Russia) -- History; Tatarstan (Russia) -- Description and travel